2019
DOI: 10.1007/s11104-019-04237-0
|View full text |Cite
|
Sign up to set email alerts
|

Field-scale variability in site conditions explain phenotypic plasticity in response to nitrogen source in Pinus radiata D. Don

Abstract: Aims. Productivity of forest ecosystems is constrained by site resource availability and utilisation at an individual tree level. A better understanding of nitrogen (N) nutrition addition to forest ecosystems is critical for maintaining optimal plantation productivity, given the influence of an environment gradient, genetics, and their interactions. Methods. We studied the aboveground growth response in a plantation setting of ten commercial P. radiata genotypes to N-fertilisation using three different N sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…The genetics of each species may be a factor in the response to the environmental conditions. Gallart, et al [23] showed that some P. radiata genotypes were more sensitive to microsite changes in soil physical properties than other, the same seed sources for both species were used across all three sites. Also, the design of these experiments was not orthogonal.…”
Section: Data Constraintsmentioning
confidence: 99%
“…The genetics of each species may be a factor in the response to the environmental conditions. Gallart, et al [23] showed that some P. radiata genotypes were more sensitive to microsite changes in soil physical properties than other, the same seed sources for both species were used across all three sites. Also, the design of these experiments was not orthogonal.…”
Section: Data Constraintsmentioning
confidence: 99%
“…Physiologically, these results suggest that more drought-tolerant genotypes are more efficient at photosynthesising and have more intact chloroplasts and chlorophyll (i.e., Photosystem II) under water stress, as suggested by recent studies in P. radiata genotypes ( Rodríguez-Gamir et al, 2019 ; Rodriguez-Gamir et al, 2020 ). Further, Gallart et al (2019) suggested that the superior growth performance of some P. radiata genotypes under dry field conditions could be due to genotype-specific responses to water stress. However, future research is required to test whether greater drought tolerance also involves greater photosynthetic rates over a wide range of genotypes ( Maxwell and Johnson, 2000 ), to determine the strength of the relationship between Y and δ 13 C.…”
Section: Discussionmentioning
confidence: 99%
“…number of dry days between precipitation events, precipitation event duration and intensity), which could be important factors for growth and stress for individual provenances. Research with other tree species has found some genotypes are more sensitive to microsite and climate than others [61]. The dendrochronological study conducted in situ on standing Californian coast redwood trees found a latitudinal pattern in climate sensitivity with a strong contrast between cooler northern rainforests and warm and dry southern forests.…”
Section: Environmental Cuesmentioning
confidence: 99%